Effects of an orthodontic primer containing amorphous fluorinated calcium phosphate nanoparticles on enamel white spot lesions. (January 2023) - Xu, Yuedan; Sun, Yi; Liu, Wei; Shi, Zhiwei; Jin, Xinyang; Xu, Jiawei; Pan, Xinni; Zhang, Zhixin; Fu, Baiping; Zhang, Ling
Abstract: Objectives: The study investigated the effects of an orthodontic primer containing amorphous fluorinated calcium phosphate (AFCP) nanoparticles on enamel white spot lesions (WSLs). Materials and methods: The AFCP nanoparticles were prepared and incorporated into Transbond XT Primer. Thirty-two human enamel slices were highly polished and randomly divided into four groups: no part covered (control), half covered with a primer containing 0 wt%, 25 wt%, and 35 wt% AFCP. Subsequently, samples were challenged by a modified pH-cycling and characterized by color measurement, micro-computed tomography, and scanning electron microscope (SEM). The bonding properties of the primers containing AFCP were assessed using shear bond strength test, and the mouse fibroblasts (L929) were employed to evaluate the cytotoxicity. Results: When the enamel was challenged by pH cycling, 25 wt% and 35 wt% AFCP groups exhibited less color change (ΔE) and less mineral loss than the control and 0 wt% AFCP groups. The SEM images showed that the original microstructural integrity and mineral deposition rate of the enamel surface were better in the 25 wt% and 35 wt% AFCP groups. In particular, the 35 wt% AFCP group exhibited the best performance after 3 weeks of pH cycling. The shear bond strength and cell viability revealed no significant difference among the tested groups (P > 0.05). Conclusion: Using the primer containing 35 wt% AFCP might be a promising strategy for preventing the occurrence and development of WSLs during orthodontic treatment.